PEMODELAN PERENCANAAN TERINTEGRASI UNTUK RANTAI SUPLAI DAN STOK PENGAMAN MULTI ESELON - Irwitadia Hasibuan; Opim Salim Sitompul; Maya Silvi Lidya (JISTech (Journal of Islamic Science and Technology), 2019)
Business environment has strong competition from year to year. This is because various changes and uncertainties fill the competition. Most of the changes or uncertainties in the business world are caused by the increasing of consumer bargaining power in business practices. Consumers have high power in determining their requests that must be fulfilled by business people. Changes or uncertainties are most of the main factors that cannot be anticipated when the business world has strong and uncertain competition. These uncertainties require business people to design an appropriate plan in order to minimize costs, especially inventory costs with consumer demand are still fullfilled. In that design plan, business people must be able to optimize the supply chain. In industrial systems, supply chain optimization and its response are strongly influenced by inventories. Inventories and its numbers are important issues in the supply chain that must be integrated with the optimization of the supply chain to manage demand uncertainty and to maintain customer service levels. This study designs an integrated planning model for supply chain and multi-echelon inventory in determining the location and the numbers of inventory in a supply chain with a general configuration with considering the uncertainty of consumer demand or  all things coming from production time